Transformasi Sosial Melalui Gereja : Menerapkan Prinsip-Prinsip Manifesto Politik Yesus dalam Menyikapi Ketidakadilan Sosial (Jurnal Pendidikan Agama dan Teologi, 2025)
This research explores the role of the church as an agent of social change by applying the principles contained in Jesus' political manifesto. In the context of increasing social injustice, the church is expected not only to function as a place of worship, but also as an entity that is active in empowering society. Through a theological and praxis approach, this study analyses how the teachings of Jesus can be implemented in concrete actions to address issues of injustice, such as poverty, discrimination and inequality. Using a qualitative method, this research collected data through interviews and case studies in various church communities that have successfully carried out social transformation. The results show that the application of these principles not only improves the quality of life of congregation members, but also strengthens solidarity and social care in the community. The findings are expected to provide new insights for churches in formulating more effective and relevant ministry strategies to address social challenges in the modern era.